Multiple octamer binding sites in the promoter region of the bovine alpha s2-casein gene. - Groenen, M A (1992)
Using a set of overlapping oligonucleotides from the promoter region of the bovine alpha s2-casein gene we have identified two nuclear factors which probably are involved in expression of this gene and the related calcium sensitive alpha s1- and beta-casein genes. One of these factors which was present in extracts of all tissues that have been tested including Hela cells turned out to be the octamer binding protein OCT-1. Oct-1 binds with different affinity to 4 sites at positions centred around -480, -260, -210 and -50. The strongest of these 4 binding sites, the one around position -50, is highly conserved in all calcium sensitive caseins of mouse, rat, rabbit and cattle. The other nuclear factor (MGF, mammary gland factor) which is specifically expressed in the mammary gland, binds to a site around position -90. This binding site is also highly conserved in all calcium sensitive caseins of mouse, rat, rabbit and cattle.